Estudio de factibilidad para la Implementación de una distribuidora de Motos, ventas de repuesto, y servicio técnico de la marca “BAJAJ”, en el cantón Pichincha, provincia de Manabí. año 2013. - Loor Saltos, Cintia Silvana (2015)
The feasibility study seeks to meet the needs of the population of Canton Pichincha, Manabí province who see motorcycles as a viable alternative means of transport for their activities, 33% of the population uses bikes as their primary mode of transportation that indicates that a distributor of motorcycles is very important to contribute to the socio economic development of this manabita canton. In this town there is a distributor of motorcycles that provide service or sell parts, at present there are several stores that provide direct loans to the population but the discomfort persisted in waiting time and the required documentation that is required a company that provides direct marketing and technical assistance, prepared the technical, legal, economic and financial studies show that the project is viable, as there is funding to launch this proyecto.se need an investment of $ 54,099.46, for the distribution of motorcycles and spare parts begin operations. The obtained results of the NPV is $ 94,612.17, shows that it is wise to invest in a motorcycle dealership in Canton Pichincha, the internal rate of return on this project is 78%, exceeding that required by the current market (8.34%), this indicates that this feasibility study is profitable for their shareholders. This company has a huge impact on society as provide jobs and contribute to the socio economic development of the Canton Pichincha